2009
DOI: 10.1002/fuce.200800091
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterisation of Pelletised Glass Electrolytes for Fuel Cells

Abstract: This paper reports on the preparation and characterisation of pelletised glass electrolytes that were fabricated with a proton conducting glass derived from a sol–gel technique, and several kinds of binders. The electrolytes, consisting of a glass powder that had been pulverised by planetary ball milling and mixed with an orthophosphoric acid binder, gave rise to a maximum proton conductivity of 1.3 × 10–2 S cm–1 measured at 80 °C and 80% relative humidity. The pore diameter of the PGE was in this case ∼2 nm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…109 Using proton conducting H 3 PO 4 as a binder, the power density of the P 2 O 5 -SiO 2 glass membrane cell was 70.3 mW cm À2 at 80 C and 75% RH, which is signicantly higher than 28.3 mW cm À2 on the same membrane but with PTFE as the binder. 127 Nakamoto et al This journal is © The Royal Society of Chemistry 2014 obtained maximum power densities of $25 mW cm À2 at 130 C and 38 mW cm À2 at 150 C using the phosphosilicate gel/polyimide composite membrane. 128 Most recently, Ishiyama et al reported the development of tungsten phosphate glass as PEM for fuel cells.…”
Section: Silica and Silica Based Glassmentioning
confidence: 99%
See 1 more Smart Citation
“…109 Using proton conducting H 3 PO 4 as a binder, the power density of the P 2 O 5 -SiO 2 glass membrane cell was 70.3 mW cm À2 at 80 C and 75% RH, which is signicantly higher than 28.3 mW cm À2 on the same membrane but with PTFE as the binder. 127 Nakamoto et al This journal is © The Royal Society of Chemistry 2014 obtained maximum power densities of $25 mW cm À2 at 130 C and 38 mW cm À2 at 150 C using the phosphosilicate gel/polyimide composite membrane. 128 Most recently, Ishiyama et al reported the development of tungsten phosphate glass as PEM for fuel cells.…”
Section: Silica and Silica Based Glassmentioning
confidence: 99%
“…158 For unsupported mesoporous materials, e.g., a-Fe 2 O 3 and P 2 O 5 -SiO 2 glass, high specic surface areas, high pore volume and narrow pore size distribution in the range of 2-3 nm would be required to maintain high water uptake and thus adequate conductivity. 91,127,135 In this case, water molecules within the mesopores play a major role in proton transport by forming protonic charge carriers through hydrogen bonding. On the other hand, size of nano or mesopores is related to the proton carrier or the dopant.…”
Section: Prospect Of Functionalized Mesoporous Silica For High Temper...mentioning
confidence: 99%